Ibuprofen ( Brufen ) as an analgesic after oral surgery - a clinical trial - Garwood, Anthony, John (My University, 1983)
Pain, swelling and trismus are common features after oral surgery, particularly after the surgical removal of impacted third molar teeth. The Maxillo-Facial and Oral Surgeon has a vast array of drugs at his disposal to combat post-operative pain, but none of these are perfect in terms of efficacy and side effects. Recently, the non-steroidal anti-inflammatory drugs have been receiving much attention as post-operative analgesics.
A dissertation submitted to the Faculty of Dentist University of the Witwatersrand, Johannesburg, in part fulfilment of the requirements for the degree of Master Dentistry in the Branch of Maxillo-Facial and Oral Surgery.
Keywords: Ibuprofen; Surgery, Oral; Clinical Trial